Extraction and characterization of polysaccharides from coconut milk residue - Mohd Nor, Nur 'Ain Najwa; Mustafa, Shuhaimi; Marikkar, Mohammed Nazrim (Halal Products Research Institute, Universiti Putra Malaysia, 2014)
The studies of dietary fibre of coconut milk residue are few. Not many research have been focused on the benefit of utilising coconut milk residue as a source of dietary fibre. The aims of this research were to extract and characterize the polysaccharides extracted from coconut residue and determining their potential used as dietary fibre. Result has shown that the polysaccharides contain about 6.95% of total carbohydrate, 20.71% of reducing sugar and minute amount of protein, approximately 0.009%. Solubility of the coconut polysaccharides is approximately 93.7 %. Result from FTIR shows that the polysaccharides from coconut residue contain β-glycosidic bond.